2012
DOI: 10.1111/j.1933-1592.2012.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Reasons Why Epistemic Reasons Are Not Object‐Given Reasons

Abstract: In this paper I discuss two claims; the first is the claim that state-given reasons for belief are of a radically different kind to object-given reasons for belief. The second is that where this last claim is true, epistemic reasons are object-given reasons for belief (EOG). I argue that EOG has two implausible consequences: (i) that suspension of judgement can never be epistemically justified, and (ii) that the reason that epistemically justifies a belief that p can never be the reason for which one believes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…See, e.g., Lewis (1988) for discussion. 5 See, e.g., Friedman (2013a) and Booth (2014). For an earlier and related thought: Higginbotham and May (1981), inspired by Levi (1967), claim that a subject's suspension of judgment should be represented with a partition of the "possible states of nature".…”
Section: Discussionmentioning
confidence: 99%
“…See, e.g., Lewis (1988) for discussion. 5 See, e.g., Friedman (2013a) and Booth (2014). For an earlier and related thought: Higginbotham and May (1981), inspired by Levi (1967), claim that a subject's suspension of judgment should be represented with a partition of the "possible states of nature".…”
Section: Discussionmentioning
confidence: 99%
“…We might also attempt to characterise withheld belief as an altogether different sort of attitude than belief, such that we understand the nature and normativity of withheld belief in and importantly different way from how we understand that of belief-for example, it has been suggested that withheld belief might best be understood as an attitude towards a question, rather than towards a proposition (e.g. see Booth 2014and Friedman 2013. Or, alternatively, we might further consider whether Sullivan-Bissett's (2018) functional account of suspension can be squared with our teleological account of belief.…”
Section: Eec: Defending the Teleological Thesismentioning
confidence: 99%
“…Important related discussions appear in Booth (2014aBooth ( & 2014b and Reisner (2008Reisner ( & 2015, and Reisner and Van Weelden (2015). ⁵⁴ See Danielsson and Olson (2007) and Reisner (2009) for the 'eyes on the prize' argument in favour of treating the incentives as direct pragmatic reasons for belief.…”
Section: The No Positive Normative Judgement Argumentmentioning
confidence: 99%